2023
DOI: 10.1002/itl2.406
|View full text |Cite
|
Sign up to set email alerts
|

Role of cybersecurity and Blockchain in battlefield of things

Abstract: The Internet of Things is an essential component in the growth of an ecosystem that enables quick and precise judgments to be made for communication on the battleground. The usage of the battlefield of things (BoT) is, however, subject to several restrictions for a variety of reasons. There is a potential for instances of replay, data manipulation, breaches of privacy, and other similar occurrences. As a direct result of this, the implementation of a security mechanism to protect the communication that occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The block is then built using the DIDLT model, which includes the block header information, hash code, timestamp, nonce message, and transaction list [14]. A private, safe BC-based approach to communication inside the battlefield of things (BoT) network recommended by Sharma et al [15]. Furthermore, they illustrated the advantages of combining cybersecurity and BC technology when implementing BoT applications [15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The block is then built using the DIDLT model, which includes the block header information, hash code, timestamp, nonce message, and transaction list [14]. A private, safe BC-based approach to communication inside the battlefield of things (BoT) network recommended by Sharma et al [15]. Furthermore, they illustrated the advantages of combining cybersecurity and BC technology when implementing BoT applications [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A private, safe BC-based approach to communication inside the battlefield of things (BoT) network recommended by Sharma et al [15]. Furthermore, they illustrated the advantages of combining cybersecurity and BC technology when implementing BoT applications [15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in patients with idiopathic intracranial hypertension (IIH) peripapillary vessel density is decreased. This might be the result of the axonal edema due to the papilledema while autoregulatory response to the low cerebral perfusion pressure leading to increased mean arterial pressure and dilation of cerebral vessels may also play an important role [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…By encrypting the data, UAVs can ensure that it remains indecipherable to unauthorized entities even if intercepted. This proactive measure minimizes the risk of data breaches and ensures that sensitive information remains accessible only to authorized recipients[90]. 2.…”
mentioning
confidence: 99%